Involvement and Autonomy of Minors in Medical Settings: Perceptions of Children Undergoing Surgery and Parents - Francisco J. Rodríguez-Domínguez; Teresa Osuna-García; Alberto Guillén; María D. Pérez-Cárceles; Eduardo Osuna (MDPI AG, 2023)
Informed consent presupposes competence and represents a formal decision by an informed person who has the legal capacity to accept medical action or participate in research. Our aim was to analyze the perceptions of minors and their parents about the age at which they consider that a minor is competent for making health decisions. A descriptive observational study was carried out in 302 minors between 12 and 17 years of age undergoing elective surgery, and 302 parents (range 30 to 62 years). Two semistructured questionnaires were designed, one for the minors and the other, for the parents. A total of 20.1% of minors and 31.1% of parents believe that patients should not make decisions related to their health until they are 18 years old. A total of 74.9% of the minors surveyed consider that from 16 years of age, the minor is empowered to make decisions. In parents, this percentage is 60%. In the pediatric setting, each case and situation must be examined individually to determine if the minor meets the condition of maturity to decide. The ideal is to promote the minor's participation in decision-making, giving them the opportunity to participate in the process in a manner appropriate to their capacity.